Removal of organochlorine pesticides using zerovalent iron supported on biochar nanocomposite from Nephelium lappaceum (Rambutan) fruit peel waste. (February 2022) - Batool, Samavia; Shah, Athar Ali; Abu Bakar, Ahmad Farid; Maah, Mohd Jamil; Abu Bakar, Nor Kartini
Abstract: Unique zerovalent iron (Fe 0 ) supported on biochar nanocomposite (Fe 0 -BRtP ) was synthesized from Nephelium lappaceum (Rambutan) fruit peel waste and were applied for the simultaneous removal of 6 selected organochlorine pesticides (OCPs) from aqueous medium. During facile synthesis of Fe 0 -BRtP, Rambutan peel extract was used as the green reducing mediator to reduce Fe 2+ to zerovalent iron (Fe 0 ), instead of toxic sodium borohydride which were used for chemical synthesis. For comparison, chemically synthesized Fe 0 -BChe nanocomposite was also prepared in this work. Characterization study confirmed the successful synthesis and dispersion of Fe 0 nanoparticles on biochar surface. Batch experiments revealed that Fe 0 -BRtP and Fe 0 -BChe nanocomposites combine the advantage of adsorption and dechlorination of OCPs in aqueous medium and up to 96–99% and 83–91% removal was obtained within 120 and 150 min, respectively at initial pH 4. Nevertheless, the reactivity of Fe 0 -BChe nanocomposite decreased 2 folds after being aged in air for one month, whilst Fe 0 -BRtP almost remained the same. Adsorption isotherm of OCPs were fitted well to Langmuir isotherm and then to Freundlich isotherm. The experimental kinetic data were fitted first to pseudo-second-order adsorption kinetic model and then to pseudo-first-order reduction kinetic model. The adsorption mechanism involves π-π electron-donor-acceptor interaction and adsorption is facilitated by the hydrophobic sorption and pore filling. After being reused five times, the removal efficiency of regenerated Fe 0 -BChe and Fe 0 -BRtP was 5–13% and 89–92%, respectively. The application of this Fe 0 -BRtP nanocomposite could represent a green and low-cost potential material for adsorption and subsequent reduction of OCPs in aquatic system. Graphical abstract: Image 1 Highlights: Fe 0 -Biochar nanocomposites were synthesized using Nephelium lappaceum peel waste. Morphology of Fe 0 -BRtP and Fe 0 -BChe nanocomposites was explored. Six organochlorine pesticides removed involving adsorption and reduction mechanism. Lower reactivity of aged Fe 0 -BChe nanocomposite, while Fe 0 -BRtP remained the same. Regenerated Fe 0 -BRtP possesses good reusability even after five cycles.